Modelling biogenic amines in fish meat in Central Europe using censored distributions - Fusek, Michal; Michálek, Jaroslav; Buňková, Leona; Buňka, František (Chemosphere, 2020)
The aim of the study is to model concentrations of selected biogenic amines in various fish species (Atlantic salmon, Atlantic cod, striped catfish) bought in retail stores in Central Europe. Since the data contains non-detectable values, statistical methods for left-censored values from the exponential and Weibull distributions are applied and used to evaluate and compare the amount of biogenic amines in fish samples. Moreover, a risk of exceeding certain limits of biogenic amine concentrations to protect human health is determined. There are relatively high concentrations of putrescine, cadaverine and histamine in almost all fish species. Moreover, there was a significant difference in mean concentrations (distributions of concentrations, respectively) of histamine, tyramine and spermidine among the species.
Keywords: Putrescine; Evropa; Biogenic Amines; Europe; biogenní aminy; Meat; kadaverin; Cadaverine; ryby; lidé; Environmental Monitoring; monitorování životního prostředí; putrescin; Spermidine; Animals; Humans; Fishes; maso; histamin; spermidin; Histamine; zvířata